ASSESSMENT OF CLINICAL FACTORS AND SERUM TESTOSTERONE ABOUT ERECTILE DYSFUNCTION IN HIV-INFECTED MEN - KUMAR, SANTOSH; MORKAR, DNYANESH; C, AKASH; SUMAN, ANJALI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to assess and correlate serum testosterone (ST) levels with erectile dysfunction (ED) and associated risk factors in human immunodeficiency virus (HIV)-positive men. Methods: The present correctional study was conducted among 75 HIV-positive patients. The study subjects were analyzed for ST levels and evaluated for ED using the international index of erectile function (IIEF-5). IIEF score was compared across depression severity assessed using a patient health questionnaire. Other variables, including age, the cluster of differentiation 4 (CD4+) count, antiretroviral treatment therapy, body mass index, and HIV duration, were also correlated with ED concerning ST levels. Results: The prevalence of ED among HIV-positive patients was 96%. The majority (54.67%) of patients had mild-moderate ED. Hypertension was found in 14.67% of the study population. The mean IIEF score was 16.15±2.93. The relationship between depression severity and IIEF score was statistically significant (p<0.001). A weak positive correlation between CD4+ count and ED was found when ST was average (rs: 0.316, p=0.163). There was no correlation between age and abnormal ST and ED [rs: −0.459, p=0.003] Conclusion: The prevalence of ED and its effect on ST levels could help in better management among HIV-infected males. Mild-moderate depression played a significant role in causing ED in association with ST levels. The study suggests that testosterone supplementation, along with optimum treatment of depression in HIV patients, can be fruitful in treating ED.